The Moderating Influence of Financial Literacy on the Relationship of Financial Attitudes, Financial Self-Efficacy, and Credit Decision-Making Intensity - LD Gadi Djou; Fitri Lukiastuti (Jurnal Akuntansi dan Keuangan, 2021)
This study aims to determine the role of financial literacy moderation on the relationship between financial attitudes and financial self-efficacy on the intensity of decision-making of the SMEs that are also the customers of KUR BNI in Ende Regency amidst the COVID-19 pandemic situation. The objects of this research are all owners of large and retail trade SMEs, car and motorcycle repairs in Ende Regency (58 SMEs). The data analysis techniques used in this research is the Moderated Regression Analysis (MRA). The results are: (1) financial attitudes has positive influence on the credit decision-making intensity on SMEs, (2) financial self-efficacy has positive influence on the credit decision-making intensity of SMEs, (3) there is a moderation impact of financial literacy on the relationship between financial attitudes and credit decision making intensity for SMEs, and (4) financial literacy is able to moderate the relationship between self-efficacy and credit decision making intensity for SMEs.